The Role of the Village Government towards Improvement Road Structure and Street Lighting in Sinjai District - Muhammad Amar; Syamsiah Hasyim; Sri Rahayu Juniati; khaerul Insan (Jurnal Ad'ministrare, 2021)
With regional autonomy, local governments are required to be able to organize good governance in terms of providing public goods and public services.The purpose of this study was to determine the role of the Terasa Village Government in Improving Road Structure and Street Lighting. This type of research is qualitative. Data collection techniques are observation, interviews and documentation. The informants were the Terasa Village Head, the Village Consultative Body, the Terasa Village, the Terasa Village Hamlet Head, and the Terasa Village community. The data analysis technique uses data reduction, data presentation and giving conclusions. The results showed that the role of the village government in improving road structure and street lighting in Terasa Village, West Sinjai District, Sinjai Regency had been implemented. However, it has not run optimally. Although several stages have been carried out, namely by proposing, facilitating and implementing. Proposing is proven by proposing road repairs. Facilitating is proven by building sports fields, PAUD buildings and posyandu. Implementation is proven by the existence of deukker, telford, concrete rebates, road expansion, sports fields, PAUD buildings, posyandu, farm roads, bridges and PLN lighting in every hamlet.